Treatment persistence of biologics among patients with psoriatic arthritis - Haddad, Amir (Arthritis Res Ther, 2021)
BACKGROUND: Persistence of biologic therapy in psoriatic arthritis (PsA) patients is an important factor in individualized patient treatment planning and healthcare policy and guideline development. OBJECTIVE: To estimate the persistence of biologic agents prescribed to PsA patients in a real-life setting as well as factors associated with improved biologic drug survival in these patients. METHODS: Patients with PsA from a large healthcare provider database with at least two consecutive dispensed prescriptions of a biologic agent indicated for PsA from January 1, 2002, until December 31, 2018, were identified and followed until medication stop date or the end of observation period. Patients were considered non-persistent whenever a permissible lag time of 6 months from the time of prescription issuance until medication filling date was exceeded. Treatment changes were based on physician decisions and patient preferences. Demographic data including age, sex, body mass index (BMI), ethnicity, smoking history, and socioeconomic status as well as Charlson comorbidity index were retrieved. Data regarding use of steroids and conventional disease-modifying anti-rheumatic drugs (cDMARDs) were also extracted. Descriptive statistics, including means (standard deviations) for continuous variables and frequencies (%) for categorical variables, were used. Persistence estimates were derived using non-parametric survival analysis using Kaplan-Meier functions, with treatment discontinuations as failure events. Cox regression hazard ratio models were conducted to investigate factors associated with drug persistence. RESULTS: A total of 2301 PsA patients with 2958 treatment periods were identified and included in the analyses. Mean age of the study population was 50.9 ± 14 years, 54% were females, 70.4% were with BMI > 25, 40% were current smokers, and 76% were with a Charlson comorbidity index > 1. The most commonly prescribed drug was etanercept (33%), followed by adalimumab (29%), golimumab (12%), secukinumab (10%), ustekinumab (8%), and infliximab (8%). While approximately 40% of patients persisted on therapy following 20 months of treatment, only about 20% of patients remained on any particular biologic agent after 5 years. Analyzing the data for all treatment periods while taking into account all lines of therapy revealed that secukinumab had a higher persistency than adalimumab, infliximab, and ustekinumab, with a log rank of 0.022, 0.047, and 0.001, respectively. Female sex and smoking were associated with lower drug persistence (HR = 1.25, 95% CI = 1.13–1.38 and HR = 1.109, 95% CI = 1.01–1.21, respectively). On analyzing the data using only the first indicated biologic line, no superiority of any single anti-tumor necrosis factor-alpha (anti-TNFα) agent was observed, while secukinumab was found to be superior as second line therapy to adalimumab, etanercept, infliximab, and ustekinumab but not to golimumab with a log rank P value of 0.001, 0.004, 0.025, and 0.002, respectively. CONCLUSIONS: In this large observational cohort studied in the era of biologic therapy, a relatively low drug persistence was observed, with female sex and smoking having a negative impact on persistency. None of the anti-TNFα agents was found to be more persistent than others as first line therapy, while secukinumab was found to be superior to other biologics when indicated as second line of therapy.